Efeitos de interação spin-órbita em anéis quânticos semicondutores - Diniz, Ginetom Souza (2007)
In this work we present a theoretical study of the spin-orbit coupling upon the electronic structure of quantum rings and dots. The contribution of Rashba, due to the structural inversion asymmetry, and the contribution of Dresselhaus, induced by the bulk inversion asymmetry, common in the III-V semiconductor group materials are included in the Hamiltonian H0, which describe a single-electron in presence of a magnetic field in the z-direction. The eigenstates of H0 are used in the calculation of the additional elements of the Hamiltonian H = H0 + HR + HD, that takes in to account both Rashba (HR) and Dresselhaus (HD) contribution in the spin-orbit coupling. The eigenvalues and eigenvectors of H are then calculated through a numerical diagonalization using a truncated base of eigenstates of H0. The electronic structure calculation were performed in quantum dots and rings of Indium Arsenate (InAs), which are of actual experimental interesting. These nanostructures (quantum rings), in general, have average radius (r0), around 30-140nm and height about d =2-5nm. The Rashba and Dresselhaus contribution induce coupling among states jn; m; ¾zi following the selection rule ¢m;m0 = §1 and are responsible by crossings and anticrossings in the electronic spectra, and also by spin state mixing for well defined magnetic field values, that can be manipulated by external parameters such the Rashba parameter, Dresselhaus, and ring geometry. Our results allow to determine speci fic regimes of magnetic field and external parameters to model in a convenient way the behavior of magneto-optical properties, decoherence process of spin states and electron g-factor, which are problems of actual interest in the semiconductor physics for spintronic device applications.